Electronic Digital Technologies in Improving Library Service - Horovyi Valery (Наукові праці Національної бібліотеки України імені В.І. Вернадського, 2022)

(untitled)
The article examines the process of forming the digital stage in the development of the information society, when integration of socially significant information resources, displayed in the past on various media, takes place, and these resources viausing digital technologies, become unified in electronic form, and are successfully usedin all spheres of social activity. At the sametime, public information exchanges supported by digital technologies with the help of computerized libraries are becoming leaders in the organization of effective use of digital resources. In the library institution itself, digitization significantly speeds up users service, increases the quality of information about available information resources, facilitates access to electronic information, and significantly improves library advisory, methodological, cultural, and educational work. Remote forms of library work with the use of digital technologies acquire qualitative improvement, and in the near future, obviously, they should become leaders in providing information to users. Today, they are developing in two main directions. The firstis related to the gradual replacement of information on paper, and other traditional carriers with digital ones used within the library institution. The second direction in remoteusers service is related to both the use of funds and the organization of libraries’ own information production, the production of information and analytical products according to the users’ requests in the information based on information mode, products that effectively reveal available library funds at the level of consideration of the main ideas reflected in the resources.